Physicochemical Properties of Various 2-Hydroxyethylammonium Sulfonate -Based Protic Ionic Liquids and Their Potential Application in Hydrodeoxygenation - Cai, Guangming; Yang, Shaoqi; Zhou, Qing; Liu, Lifei; Lu, Xingmei; Xu, Junli; Zhang, Suojiang (Frontiers in Chemistry, 2019)
In order to get the regularities of physicochemical properties of hydroxy protic ionic liquids (PILs) and broaden their potential application, a series of 2-hydroxyethylammonium sulfonate-based PILs were synthesized through proton transfer reaction and characterized by NMR and FT-IR and elemental analysis. Their phase transfer behavior (Tm) and initial decomposition point (Td) were characterized by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), respectively. Meanwhile, the regularities of density (ρ), viscosity (η) and electrical conductivity () of synthesized PILs at different temperatures were measured. The results indicated their physicochemical properties were tightly related with their structures and the interactions between cations and anions. In addition, the dissociation constants (pKa) of synthesized PILs were obtained by acid-base titration, which revealed that all synthesized PILs had pKa exceeding 7 and their cations were the crux of determining the pKa value. What’s more, several synthesized PILs with low melting temperature also showed potential application in the deoxidation reaction of cyclohexanol as they had conversion rate of approximating 100 % and selectivity of cyclohexane or cyclohexene about 80%.